Conditions associated with turnovers in basketball - Bazanov, B.; Vohandu, P. (World Congress of Performance Analysis of Sport VIII, 2008)
Results of our analysis show that frequency of turnovers is higher, if teamwork intensity index is low (table 1, rule 6) and sum of elements used in offensive zone is under two (table 1, rule 7). Commonly it means, that ball handler is crossing the middle line and is in trouble to go along with organized set offence. Usually the problems arise when inactive team-mates do not seek for the free places to receive the pass. The associative rules show that frequency of turnovers is very high if there is the set offence, it starts with inbound in defensive zone and sum of elements in offensive zone is two or lower (table 1 rule 2). The frequency of turnovers is also high in situations with one or two dribbles in defensive zone during the transition phase and the sum of used elements in the offensive zone is under two with low teamwork intensity (see table 1 rule 1). Rules 8 and 9 shows us, that the opponents` active defence also increases the number of turnovers. Particularly it happens in situations, when offence begins with inbound in defensive zone and the players use dribbling during the transition. Based on this information we can conclude that most turnovers happened during the transition period or directly in the beginning of the set offence under the pressure of the opponent team. Another question is how to overcome these problems? In table 2 there are shown the conditions to avoid the turnovers. We can see, that with the purpose to minimize the number of turnovers team should increase teamwork intensity index (table 2, rule 1). Rule 2 in table 2 shows us the importance of winning the defensive rebound. Both, rules 2 and 5 tell us, that the effective defensive activity of the team is significantly influencing the quality of the team offence. The analysis also shows that it is important to use more passes in defensive zone during the transition phase, particularly in the situations, when opponent uses the active forms of defence. Based on the results we suggested coaching staff how to recognize and prevent situations leading to the turnover.